Pneumonia as a Secondary Complication Related to Inhaled Corticosteroid Combination Treatment for Chronic Obstructive Pulmonary Disease with Eosinophilic Phenotype Patient - Wibowo, Adityo; Saputra, Tetra Arya (CV. Jasa Sukses Abadi, 2024)
Chronic obstructive pulmonary disorder (COPD) is a progressive respiratory condition characterized by chronic inflammation, proteases and antiproteases imbalance, and airway remodeling. Several hypotheses, including immune dysregulation, microbial colonization, and environmental triggers, explain the underlying cause of the deteriorating state and recurrence of exacerbations in COPD. Eosinophils, one of the inflammatory mediators, are involved in about 30% of cases of COPD. In COPD with an eosinophilic phenotype, specific therapy recommendations include inhaled corticosteroids (ICS) combined with a long-acting bronchodilator therapy typically includes the combination of inhaled corticosteroids (ICS) (e.g., fluticasone, budesonide) and a long-acting bronchodilator (LABA) (e.g., formoterol, salmeterol) to improve airflow and reduce inflammation. While ICS therapy is beneficial, side effects of pulmonary infections become more likely as the dose increases, particularly with prolonged use. The risk of pneumonia can be managed through dose optimization and careful patient monitoring.